Ethnomedicine in Ammatoa maternal care: Lexicon, semantic categories, and speech practices - Ningsih, Sri; Bohari, Nurul Hidayah; Jusni, Jusni (Jurnal CULTURE (Culture, Language, and Literature Review), 2025)
This article maps the maternal–neonatal ethnomedicine of the Ammatoa indigenous community, detailing lexicon, semantic categories, and speech practices that scaffold mother–infant care. Based on an inventory of 26 medicinal plants and practice notes, terms are grouped into four clusters: (1) materials/remedies, (2) actions, (3) prayers, and (4) symptoms. Findings show that the local pharmacopeia is tightly coupled with ritual utterances; water ‘bound’ by prayer soothes the mother, underpins household hygiene, and frames a stepwise pathway from comfort care to referral when danger signs emerge. The coexistence of sanro pammana (traditional birth attendant) and midwife indicates a practical division of labor, sanro on ritual/comfort, midwife on clinical actions, while the family, especially the husband, supports logistics and decision-making. Linguistically, the lexicon is transmitted in Konjo interspersed with Indonesian, functioning not only as labels but as a social protocol that orchestrates recovery rhythm and referral compliance. Practical implications include a bilingual glossary and culturally attuned health communication materials for mother–infant care.